2012
DOI: 10.1590/s1676-24442012000400009
|View full text |Cite
|
Sign up to set email alerts
|

Primary plasmacytoma of the thyroid gland: a case report of a rare neoplasia

Abstract: reLato de caso case report Extramedullary plasmacytoma comprises 3%-5% of all plasma cell neoplasms, and approximately 80% of the cases occur in the upper respiratory tract. Primary thyroid plasmacytomas (PTP) are rare tumors. The authors report a case of PTP in a male patient with dyspnea and dysphagia. Physical examination and computerized tomography (CT) scan revealed a solid tumor affecting the thyroid gland, measuring 12 cm in its greatest dimension. Surgical biopsy was performed. Microscopy revealed a hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 13 publications
(10 reference statements)
0
3
0
Order By: Relevance
“…The electronic searches yielded 1143 articles (PubMed: 418, Web of Science: 292, Embase: 265, and Scopus: 168) and 82 studies reporting 102 individuals were included in this systematic review 17–98 (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The electronic searches yielded 1143 articles (PubMed: 418, Web of Science: 292, Embase: 265, and Scopus: 168) and 82 studies reporting 102 individuals were included in this systematic review 17–98 (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…Most cases were primary and extraosseous lesions. However, both extraosseous and intraosseous lesions result in a variety of findings, including swelling associated or not with pain, facial asymmetry, numbness, paraesthesia, and hoarseness 17–98 . Notably, the findings indicated that most cases had a diagnosis of plasmacytoma (extramedullary or solitary of bone) and the remaining ones had systemic involvement by PCM.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation